PENERAPAN PERLINDUNGAN HAK TERSANGKA DALAM PROSES PEMERIKSAAN OLEH PENYIDIK DI WILAYAH HUKUM KEPOLISIAN RESOR INDRAGIRI HILIR - Ismail Saleh; Evi Deliana; Ferawati ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
The suspect is granted a set of rights by the Criminal Procedure Code through Articles 50 through 68. But in reality the protection and enforcement of human rights is still far from satisfactory and also in the process of examination is still not really done, it is because there is no sanction laws that can be delegated to law enforcement officers and state apparatus. In addition there is abuse of power by investigators or law enforcement officers against suspects or defendants.The type of research used in the writing of this law is juridical sociological legal research is a study that wants to see the correlation between law and society, so as to reveal the effectiveness of law enforcement in society and mengidintifikasi unwritten law applicable to the community. The nature of this research is descriptive. This study uses secondary data that is ready-made data.The result of this research is the application of the protection of suspect rights in the investigation process by the investigator in the legal area of Resort Police Indragiri Hilir not optimal yet in accordance with the prevailing laws and regulations namely Law Number 48 Year 2009 regarding Judicial Power, Law Number 39 Year 1999 regarding Human Rights and Law No. 8 of 1981 on Criminal Procedure Code (KUHAP). Unacceptable action in the investigation process is based on the visa result known that the police conduct maltreatment of the suspect, the absence of an arrest warrant during arrest and unauthorized search to the head of RT and homeowners. Obstacles in applying the protection of the suspect's right in the investigation process by the investigator in the Law Territory of the Indagiri Hilir Resort Police in the form of a violation of the law against the right to know clearly and the language understood by him about what is suspected and what is indicted, the right to freely give information to the investigator and such judges are upfront, and the right to a private doctor's visit. The suspect's legal effort is to use a lawyer to obtain his / her rights as a suspect and the police committing an offense at the examination stage get disciplinary sanction by the police agency.